2015
DOI: 10.1016/j.gaitpost.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shoe sole geometry on toe clearance and walking stability in older adults

Abstract: Thirty-five percent of people above age 65 fall each year, and half of their falls are associated with tripping: tripping, an apparently 'mundane' everyday problem, therefore, significantly impacts on older people's health and associated medical costs. To avoid tripping and subsequent falling, sufficient toe clearance during the swing phase is crucial. We previously found that a rocker-shaped shoe sole enhances toe clearance in young adults, thereby decreasing their trip-risk. This study investigates whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Bassett & Walsh (2011) [83] shoes improved postural stability among older adult subjects; Brenton-Rule D'Almeida, Bassett, Carroll, Dalbeth and Rome (2014) [84] found that sandals may negatively impact postural stability through their study of women with RA (mean age 67.6 years); Thies et al (2015) [85] found that sole geometry may have an effect on toe clearance and stability during walking; and finally Yamaguchi,…”
Section: Figure 5 Pathway For Use Of Footwear Linked To Fallsmentioning
confidence: 99%
“…Bassett & Walsh (2011) [83] shoes improved postural stability among older adult subjects; Brenton-Rule D'Almeida, Bassett, Carroll, Dalbeth and Rome (2014) [84] found that sandals may negatively impact postural stability through their study of women with RA (mean age 67.6 years); Thies et al (2015) [85] found that sole geometry may have an effect on toe clearance and stability during walking; and finally Yamaguchi,…”
Section: Figure 5 Pathway For Use Of Footwear Linked To Fallsmentioning
confidence: 99%
“…Thies et al also report higher MTC over tactile paving of the kind used for the visually impaired, suggesting that subjects perceive an increased POT and compensate by increasing MTC (Thies et al, 2011). Surface inclination also affects MTC with both declines and inclines causing an increase in MTC (Thies et al, 2015(Thies et al, , 2011. Footwear also influences MTC.…”
Section: Minimum Toe Clearance To Infer Probability Of Trippingmentioning
confidence: 96%
“…For example, slippers cause a decrease in MTC when compared to well-fitted shoes, implying a higher POT (Davis et al, 2016). Increasing the angle of the shoe sole to the ground at the toe region of the shoe (rocker angle) has been shown to increase MTC (Thies et al, 2015(Thies et al, , 2011. High heeled shoes can also increase MTC, a possible reaction to a perceived increase in POT, while high-top shoes have the opposite effect on MTC, which may be a consequence of reduced ankle mobility and dorsiflexion during swing.…”
Section: Minimum Toe Clearance To Infer Probability Of Trippingmentioning
confidence: 99%
See 1 more Smart Citation
“…A posterior 10-degree heel bevel is optimal [41]. To enhance toe clearance during the swing phase of the leg, a bevelled nose of 10-15 degrees (this is called a rocker angle) is advised [42]. See Fig.…”
Section: Bevelled Heel and Bevelled Nose Of The Shoementioning
confidence: 99%